PENGARUH INFLASI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Erika Feronika Br Simanungkalit (Journal of Management Small and Medium Enterprises (SMEs), 2020)
This study aims to determine the effect of inflation on economic growth in Indonesia since 1983-2014.The analysis used in this research is descriptive analysis and econometric analysis. Econometricanalysis in this study uses simple linear regression with the Ordinary Least Squre (OLS) method.The results showed that the independent variable influencing the dependent variable was proven fromthe probability value (F-statistic) smaller than α = 5%. T Test results show that the Inflation variableinfluences Economic Growth with a probability value smaller than α = 5%. The results of thecoefficient of determination test indicate that the dependent variable can be explained by theindependent variable by 74.7588% and the remaining 25.2412% is explained by other variablesoutside the model. Keywords : Economic Growth, Inflation & Ordinary Least Squre (OLS)